Students’ Perception of the Role of Cue Cards to Help Students Improve Their Speaking Abilities in Senior High School 1 Ajibarang - Dwi Suweni (Proceedings Series on Social Sciences & Humanities, 2023)
The research entitled "Students' Perception of The Role of Cue Cards for Improving Students’ Speaking Skills" is intended to investigate whether the actual role of using cue cards in improving and enhancing students' speaking skills is effective or not for students of SMA N 1 Ajibarang. The subjects of this study were grade 10 students of SMA N 1 Ajibarang. The population of this study is class 10. While the sample of this study is 4 classes of grade 10. The data of this research were obtained through observation and questionnaires as the research instrument. The results of this study indicate that the use of cue cards has a strong influence on students in the learning process, student motivation, and the output of learning activities.